Novel orally bioavailable EZH1/2 dual inhibitors with greater antitumor efficacy than an EZH2 selective inhibitor - Honma, Daisuke; Kanno, Osamu; Watanabe, Jun; Kinoshita, Junzo; Hirasawa, Makoto; Nosaka, Emi; Shiroishi, Machiko; Takizawa, Takeshi; Yasumatsu, Isao; Horiuchi, Takao; Nakao, Akira; Suzuki, Keisuke; et al. (Cancer science, 2017)
Polycomb repressive complex 2 (PRC2) methylates histone H3 lysine 27 and represses gene expression to regulate cell proliferation and differentiation. Enhancer of zeste homolog 2 (EZH2) or its close homolog EZH1 functions as a catalytic subunit of PRC2, so there are two PRC2 complexes containing either EZH2 or EZH1. Tumorigenic functions of EZH2 and its synthetic lethality with some subunits of SWItch/Sucrose Non‐Fermentable (SWI/SNF) chromatin remodeling complexes have been observed. However, little is known about the function of EZH1 in tumorigenesis. Herein, we developed novel, orally bioavailable EZH1/2 dual inhibitors that strongly and selectively inhibited methyltransferase activity of both EZH2 and EZH1. EZH1/2 dual inhibitors suppressed trimethylation of histone H3 lysine 27 in cells more than EZH2 selective inhibitors. They also showed greater antitumor efficacy than EZH2 selective inhibitor in vitro and in vivo against diffuse large B‐cell lymphoma cells harboring gain‐of‐function mutation in EZH2. A hematological cancer panel assay indicated that EZH1/2 dual inhibitor has efficacy against some lymphomas, multiple myeloma, and leukemia with fusion genes such as MLL‐AF9, MLL‐AF4, and AML1‐ETO. A solid cancer panel assay demonstrated that some cancer cell lines are sensitive to EZH1/2 dual inhibitor in vitro and in vivo. No clear correlation was detected between sensitivity to EZH1/2 dual inhibitor and SWI/SNF mutations, with a few exceptions. Severe toxicity was not seen in rats treated with EZH1/2 dual inhibitor for 14 days at drug levels higher than those used in the antitumor study. Our results indicate the possibility of EZH1/2 dual inhibitors for clinical applications. We developed novel, orally bioavailable EZH1/2 dual inhibitors that strongly and selectively inhibited methyltransferase activity of both EZH2 and EZH1. EZH1/2 dual inhibitor showed greater antitumor efficacy than EZH2 selective inhibitor in vitro and in vivo against diffuse large B‐cell lymphoma cells harboring gain‐of‐function mutation in EZH2. Severe toxicity was not seen in rats treated with EZH1/2 dual inhibitor for 14 days at drug levels higher than those used in the antitumor study.